2018
DOI: 10.1108/jkm-03-2017-0106
|View full text |Cite
|
Sign up to set email alerts
|

Transforming collective knowledge into team intelligence: the role of collective teaching

Abstract: Purpose The purpose of this study is to explore the pivotal role that collective teaching plays in knowledge transfer between new product development teams. This study develops a theoretical model of collective teaching, where team intelligence is its consequence and learning orientation cognitive skills are moderators. Design/methodology/approach Based on a questionnaire survey of 156 pairs of new product development project teams of information technology firms, the authors used partial least squares to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 103 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…Qualitative analysis of the research revealed that patient empowerment evolves through three levels of empowerment, in which the patient becomes increasingly empowered to use their knowledge in everyday decisions to pursue not only their own but also community health behaviors [ 14 , 18 , 51 , 60 , 74 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Qualitative analysis of the research revealed that patient empowerment evolves through three levels of empowerment, in which the patient becomes increasingly empowered to use their knowledge in everyday decisions to pursue not only their own but also community health behaviors [ 14 , 18 , 51 , 60 , 74 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed that to stimulate knowledge sharing in mediating structures and at macro level for patient knowledge empowerment transformational leadership manifestations are important [ 17 , 51 , 84 , 93 ], supportive culture of these organizations [ 16 , 18 , 51 , 74 , 91 , 93 ], and a less formalized and centralized structure of the organizations [ 17 , 74 , 93 ]. Regardless of the fact that mediating patient structures are mostly informal and patient community organizations are formalized, through a less formalized and centralized organizational structure, active social interaction between members of the organization is created to ensure knowledge sharing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the network information has a certain degree of uncertainty. After obtaining a large amount of information, it needs to be screened out and valuable commentary information can be screened out to better play the role of group wisdom [9]. Therefore, in order to synthesize market opinions, this paper collects online user reviews through group wisdom, and integrates consumer satisfaction into product family design, that is, to obtain product family characteristics with high attention according to comments, so as to classify product family modularily and combine with product family platform to provide reliable suggestions for product family development and design.…”
Section: Gathering Group Intelligence Online User Commentsmentioning
confidence: 99%